Millennial Generation (Generation Y) in Surabaya Construction Projects: Perspective towards Generation Y Characteristics - Alfonsus Dwiputra Widjaja (Petra Christian University, 2019)
Generation Y has important role in construction projects and will dominate the Indonesia demographic bonus period. Each generation has unique characteristics that impact ethics, work relations, attitudes toward change, and organization view. The purpose of this research is to analyze generation Y characteristics in Surabaya construction projects. Understanding its characteristics may maximize the potency and overcome the generation gap. The research begins with finding variables relate to generation Y characteristics. Data analysis is done by descriptive, inferential and factor analyses. According to generation Y, the highest characteristics that they agree is like to develop continuously. Generation Y in consultant and contractor companies has different perspectives toward their characteristics. Generation Y characteristics can be grouped into five groups, namely short-term thinking, creative, multitasking, detailed work instruction, and individualist. Mentoring and guidance is one of the methods that can be done to manage generation Y.